Impact of rurality on melanoma diagnosis in Utah - Tawnya L Bowles; Carol Sweeney; John Snyder; Jesse Gygi; Brad Bott; Daniel Wray; Timothy J Yeatman; William T Sause (Melanoma Management)
Aim: To analyze trends in Utah melanoma diagnosis and study the impact of rurality. Patients & methods: State-wide melanoma incidence was calculated using Surveillance, Epidemiology, and End Results data (2005–2013). A subset of 5199 patients treated in an integrated healthcare system was further stratified for urban or rural residence. Results: Early-stage tumors accounted for most of the increase in melanoma incidence over time. Age-adjusted melanoma incidence rate was higher in rural counties (46.7 vs 39.4). Anatomic site and stage did not differ between rural and urban patients. Rural patients were more commonly diagnosed by a local primary care provider. Conclusion: Rurality had an impact on melanoma diagnosis in the specialty and location of the diagnosing provider.